A spectrum of retinal vasculature measures and coronary artery disease. (January 2018) - Wang, Sarah B.; Mitchell, Paul; Liew, Gerald; Wong, Tien Yin; Phan, Kevin; Thiagalingam, Aravinda; Joachim, Nichole; Burlutsky, George; Gopinath, Bamini
Abstract: Background and aims: We aimed to comprehensively describe a spectrum of retinal vessel measures including fractal dimension (Df ) and their associations with indices of coronary artery disease (CAD) extent and severity, as well as hypertension and diabetes. Methods: The Australian Heart Eye Study (AHES) is an observational study that surveyed 1680 participants presenting to a tertiary referral hospital for the evaluation of potential CAD by coronary angiography. A range of newer retinal vessel geometric measures (Df, curvature tortuosity, and branching angle) were quantified from retinal photographs using semi-automated software, the Singapore 'I' Vessel Assessment (SIVA) tool. A combined retinal score was constructed, aiming to assess the joint effect of multiple retinal vessel parameters on CAD, comprising of those variables that were most strongly significant in multivariate analysis - Df, arteriolar curvature tortuosity, and retinal arteriolar calibre. CAD was objectively quantified using a range of measures obtained from coronary angiography. Results: A total of 1187 participants had complete data on retinal vessel measurements and coronary vessel evaluation. Retinal vascular Df and curvature tortuosity decreased with increasing age; women had significantly lower Df than men ( p <0.003). Straighter retinal vessels were associated with CAD extent and Gensini scores in multivariable analysis ( p <0.02). Accounting for media opacity by sub-group analysis in pseudophakic patients, the combined retinal score was associated with stenosis greater than 50% in any coronary artery segment (vessel score) and obstructive coronary stenosis in all three main coronary arteries (segment score) ( p = 0.01). Lower Df and narrower arteriolar branching angle were associated with CAD vessel score ( p <0.03). In sex-stratified multivariate analyses, straighter arterioles were associated with greater odds of CAD in men, and narrower venular branching angle was associated with CAD in women. Conclusions: A range of retinal vessel measures were associated with CAD extent and severity. A sparser retinal microvascular network (smaller Df ) was associated with older age and female gender. After accounting for the impact of media opacity, retinal vessel measures were associated with more diffuse and severe CAD. Highlights: Retinal vessel measures are associated with CAD extent and severity. A sparser retinal microvascular network (smaller Df ) is associated with older age and female gender. After accounting for the impact of media opacity, retinal vessel measures are associated with more diffuse and severe CAD.